The Relationship between Technological Pedagogical and Content Knowledge (TPACK) and Technology Integration Self Efficacy (TISE) of Biology Teachers - Soraya, Yenni; Nurmaliah, Cut; Khairil, Khairil; Muhibbuddin, Muhibbuddin; Safrida, Safrida (Jurnal Penelitian Pendidikan IPA, 2023)
High school biology teachers' good TPACK and TISE abilities will affect students' Biology learning outcomes. This study aims to determine the TPACK and TISE abilities of high school biology teachers in Banda Aceh City. this research is a survey research with a quantitative approach with a correlational design. The population in this study were all high school biology teachers in Banda Aceh City and using the total sampling method, the total sample was 49 high school biology teachers. Data collection was carried out by means of questionnaires, interviews and observations. The TPACK questionnaire contains 36 question items and the TISE questionnaire contains 28 question items. For interviews there are 25 question items. TPACK observations contain 28 observation items and TISE contains 14 observation items. For correlation values between TPACK and TISE, the Pearson Product Moment correlation formula is used. Based on the results of the study, it is known that there is a significant and positive correlation between the TPACK and TISE abilities of biology teachers at public high schools in Banda Aceh City